2017
DOI: 10.1002/2017jb014003
|View full text |Cite
|
Sign up to set email alerts
|

On the physics‐based processes behind production‐induced seismicity in natural gas fields

Abstract: Induced seismicity due to natural gas production is observed at different sites worldwide. Common understanding states that the pressure drop caused by gas production leads to compaction, which affects the stress field in the reservoir and the surrounding rock formations and hence reactivates preexisting faults and induces earthquakes. In this study, we show that the multiphase fluid flow involved in natural gas extraction activities should be included. We use a fully coupled fluid flow and geomechanics simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 82 publications
1
78
0
Order By: Relevance
“…This will result in a more complex state of stress on the fault, depending on the size of these lenses. Additionally, incorporating the different responses of gas and water in the reservoir generates a more complex stress state (Zbinden et al, 2017). Within the Slochteren Formation, compaction may be heterogeneous due to variations in porosity; this can also change the state of stress along the fault.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This will result in a more complex state of stress on the fault, depending on the size of these lenses. Additionally, incorporating the different responses of gas and water in the reservoir generates a more complex stress state (Zbinden et al, 2017). Within the Slochteren Formation, compaction may be heterogeneous due to variations in porosity; this can also change the state of stress along the fault.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the reservoir modelling and history matching, which suggest most faults are not sealing. However, if faults were (partially) sealing, the delayed pressure response would influence fault slip (Zbinden et al, 2017). Diffusion of pressure from the overburden and underburden formations and fault in response to the reservoir depletion would also influence slip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear and normal stresses are calculated from the stress tensor according to the plane of weakness orientation relative to the principal stresses. A similar approach has been used extensively to model the response of fault zones subjected to fluid injection (Cappa & Rutqvist, ; Rinaldi, Jeanne, et al, ; Rinaldi, Rutqvist, & Cappa, ; Rutqvist et al, ) or extraction (Zbinden et al, ). Such a model can be further extended, to account for increasing complexity, being successfully applied also for a full 3‐D formulation (e.g., Rinaldi et al, ; Rutqvist et al, ), as well as for studying the ground surface response by dynamic rupture modeling (Cappa & Rutqvist, ; Rinaldi, Jeanne, et al, ) and with slip rate‐dependent friction evolution (Urpi et al, ).…”
Section: Coupled Geomechanical Modelmentioning
confidence: 99%
“…Both effects are caused by the development of small vertical compaction strains (ε < 1%) in the reservoir as the effective stress increases during reduction of the pore pressure, typically by several tens of MPa (Morton et al, 2001;Mallman & Zoback, 2007). Reservoir compaction is generally assumed to be poroelastic (Bourne et al, 2014;Dempsey & Suckale, 2017;Zbinden et al, 2017), hence reversible, rate insensitive, and easily quantified (Wang, 2000). However, both field data (Santarelli et al, 1998) and experimental studies have shown that, even at the small reservoirs strains pertaining to hydrocarbon production, a significant part of the deformation behavior of sandstone reservoirs is inelastic (Bernabe et al, 1994;Schutjens et al, 1995;Hol et al, 2015Hol et al, , 2018Yale & Swami, 2017;Pijnenburg et al, 2018Pijnenburg et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%